Farmer Communication Effectiveness Of Rice Farmer Groups In Waihatu Village, West Kairatu Sub-District, West Seram District - Sahaji Latuamury; E. Ch. Pappilaya; P. M. Puttileihalat (International Journal of Technology and Education Research, 2023)
Communication is a daily activity that can never be separated from human life. Communication activities are exchanging messages with people we want to give messages to. So no wonder communication is also very important in the development of the agricultural world. In this study, the formulation of the problem studied is how the process of implementing farmer groups communication in Waihatu village, West Kairatu sub-district. What are the obstacles encountered by farmer group members in communicating with other farmer group members in Waihatu Village, West Kiaratu District. How is the solution to maintain the effectiveness of communication between members of farmer groups and other farmer groups in the village of Waihatu? with other farmer groups in Waihatu village, West Kairatu District. The purpose of this study was to describe the application of communication used by the rice farmer group of Waihatu Village, West Kairatu District. Then Identify the obstacles that are found in carrying out rice farmer group communication in Waihatu Village, Kairatu District.And Explain the strategies that are done to keep farmer group communication effective.The research method used is qualitative and quantitative research. Data collection is done by means of observation, documentation and interviews, and questionnaires then for data analysis techniques using SWOT Analysis Techniques to identify the problems studied. First, the application of communication carried out by the Waihatu Village rice farmer group, on the application of communication effectiveness which includes cognitive, affective, and behavioral aspects. The second obstacles found in the rice farmer group of Waihatu village itself in the form of technical, semantic, and psychological barriers.The third strategy in maintaining effective communication in the waihatu village farmer group is to increase meetings and cooperation between groups as well as the city government and the local agricultural office, increased knowledge also applies to farmers so that communication can be even more effective.